Click to Chat

1800-2000-838

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
`        a=(/3+/2)^-3b=(/3-/2)^-3Then(a+1)^-1 + (b+1)^-1  =?`
8 months ago

SOVON SARKAR
11 Points
```							Let /3-/2=x. Therefore /3+/2=1/xNow a=x^3 and b=1/x^3.  a+1=x^3+1........(1)Now b+1=1/x^3 + 1=(x^3+1)/x^3=(a+1)/x^3   [using (1)]Therefore 1/(b+1)=x^3/(a+1) Now 1/(a+1) + 1/(b+1) = 1/(a+1)+x^3/(a+1)=(x^3+1)/(a+1)=(a+1)/(a+1)=1  [using (1)]
```
8 months ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »

## COUPON CODE: SELF10

### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution

### Course Features

• 101 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions